Teachers' Differentiated Instructional Strategies to Accommodate Gifted and Non-Gifted Students' Characteristics in Learning English at Dyatmika Elementary School - Ketut Serli Winarti; Luh Putu Artini; Kadek Sonia Piscayanti (Universitas Islam Negeri Palopo, 2026)
The current study aimed at analyzing the teachers’ differentiated instructional strategies to accommodate gifted and non-gifted students’ characteristics in learning English at Dyatmika Elementary School. A qualitative approach was adopted in the form of a case study concerning the students’ characteristics, implementation of differentiated instructional strategies, and the challenges faced by the English teachers in implementing the strategies for gifted and non-gifted students. There were two English teachers involved as a research sample by using the total sampling technique. The data were collected through observation, interview, checklist, and open-ended questionnaire survey. The instruments were an observation sheet, an interview guide, a check-list, and an open-ended questionnaire. The data were analyzed by conducting qualitative data analysis consisting of three steps: data reduction, data display, and conclusion drawing. The findings show that differentiated instructional strategies are systematically implemented in second-grade English classrooms to address the distinct characteristics of gifted and non-gifted students. Teachers adjust content, process, product, and learning environment to accommodate differences in motivation, pace, creativity, and independence; however, the implementation remains challenging due to time constraints, limited resources, pacing differences, and classroom management complexity. These findings highlight both the necessity and the practical challenges of sustaining differentiated instruction in mixed-ability classrooms.